A cross-sectional study on psychiatric comorbidity, coping strategies, and quality of life in women diagnosed with breast and cervical cancers attending a tertiary care center in South India - Susila Sharmili Kumaravel; Niranjana Devi Andisamy; Praveena Daya Appadurai; Thenmozhi Lakshmanamoorthy; Ayyakutti Muni Raja; Rajeshwari Kathiah; Arumuganathan Shanmugavinayagam (Industrial Psychiatry Journal)
Background: Breast and cervical cancers pose significant health challenges for Indian women, impacting their psychological well-being and quality of life. Aim: To compare psychiatric morbidity, explore coping strategies, and evaluate quality of life among women with these cancers. Materials and Methods: A cross-sectional observational study among women aged 18 years and above attending a tertiary care hospital Oncology unit diagnosed first time with breast or cervical cancer, providing informed consent, were recruited by purposive sampling between September 2019 and August 2020. Using a semi-structured questionnaire, sociodemographic and clinical details were collected. Participants were interviewed using Mini International Neuropsychiatric Interview (MINI) version 6, Hamilton Depression Rating Scale, Hamilton Anxiety Rating Scale, Coping Checklist, and WHOQOL-BREF. Descriptive and inferential statistics were used. A P value of < 0.05 was considered significant. Results: Sixty-eight participants (34 in each group) were recruited from a tertiary care hospital’s Oncology unit between September 2019 and August 2020. Comorbid psychiatric illnesses were found in 41.2% of cervical and 32.4% of breast cancer participants. Major depressive disorder (20.6% cervical; 8.8% breast) and generalized anxiety disorder (8.8% each) were common. Emotion-focused coping was prevalent, while negative distraction was least used. Quality of life was lowest in social relationships, physical health, and psychological health domains, with no significant intergroup differences. Conclusion: The high prevalence of psychiatric morbidities, poor coping strategies, and impaired quality of life imply that healthcare providers need to be culturally sensitive and integrate mental health screening and support services into routine cancer care.